Prediction Analysis of Customer Satisfaction Levels at Company XXX Using the Classification Method - Evi Purnamasari; Priscila Yuni Praditya, Ni Wayan; Dwi Asa Verano (Jurnal Informasi dan Teknologi, 2024)
Service in companies operating in the service system plays a very important role, including in one of the companies in the city of Palembang which we call Company XXX. The level of customer satisfaction with service at Company XXX needs to be considered in order to find out how satisfied customers are with the service system provided by Company XXX. On this occasion the researcher aims to analyze and predict the level of customer satisfaction at Company XXX using the C4.5 classification method. Customer satisfaction is an important factor in maintaining customer loyalty and improving company performance. Using historical customer data for the last 1 year, we apply the C4.5 algorithm to predict customer satisfaction levels. The research results show that the C4.5 method has quite high prediction accuracy, which reaches 83%. It is hoped that the findings from this research can help XXX Company identify the factors that influence customer satisfaction and be able to take strategic steps to improve the quality of service.